2022
DOI: 10.1002/jctb.7035
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of dimethyl terephthalate to terephthalic acid on Nb‐modified HZSM‐5 zeolite catalysts

Abstract: BACKGROUND: Whether waste polyethylene terephthalate (PET) can be effectively recycled is one of the main challenges of the current environmental problems. The hydrolysis of dimethyl terephthalate (DMT) to terephthalic acid (TPA) over Nb-modified HZSM-5 zeolite was studied. Nb/HZSM-5 zeolites with different loadings were prepared and characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, NH 3 -temperature programmed desorption and pyridine adsorption infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The transmission peak at 2500–3000 cm –1 attributed to the hydroxyl group stretching vibration in the carboxyl group, and the transmission peak at 1684 cm –1 attributed the stretching vibration to the CO in the carboxyl group . The peaks at 1575, 1509, and 1423 cm –1 represented the vibration of the benzene ring skeleton in TPA . The vibration peak at 1284 cm –1 represented the vibration of C–O .…”
Section: Resultsmentioning
confidence: 99%
“…The transmission peak at 2500–3000 cm –1 attributed to the hydroxyl group stretching vibration in the carboxyl group, and the transmission peak at 1684 cm –1 attributed the stretching vibration to the CO in the carboxyl group . The peaks at 1575, 1509, and 1423 cm –1 represented the vibration of the benzene ring skeleton in TPA . The vibration peak at 1284 cm –1 represented the vibration of C–O .…”
Section: Resultsmentioning
confidence: 99%
“…Wherein, NaY zeolite has a high specific surface area and large pore size, provides adjustable acidic and basic sites that favor the reaction, and can be modulated in acidity and basicity when loaded with metal oxides [96] . Thus, Tang et al utilized the MgO/NaY as a modified mesoporous catalyst for the methanolysis of PET wastes, creating an efficient and feasible way to solve the plastic crisis of PET [Figure 9C] [97] . It was demonstrated that both PET conversion and dimethyl terephthalate (DMT) yield increased with rising catalyst basicity [Figure 9D].…”
Section: Polyester Plastic Upcyclingmentioning
confidence: 99%
“…The conversion was influenced by temperature changes; the DMT conversion and TPA yield increased gradually with an increase in temperature. At 160°C, DMT conversion and TPA yield were 33.4 and 21.8%, respectively; at 200°C, the DMT conversion was complete and the rate was 100% (DMT yield = 93.5%) [ 42 ]. Similar to the aminolysis products (BFTA, BHETA, DAA, and DHTA), the methanolysis product, DMT, can be applied to biological upcycling as a substrate after applying a suitable hydrolysis process to produce TPA and EG from DMT.…”
Section: Chemical Depolymerizationmentioning
confidence: 99%